Results of an Experiment to Study the Succession of Ground Flora Species under Forest Plantations Raised on Old Agricultural Land in the New Forest, Dehra Dun, India - Krishnaswamy, V. S. (Indian Forester, 1954)
Small ground flora quadrats, one each, were laid in plantations of Gmelina arborea, Tectona grandis, Shorea robusta, Pinus longifolia and Dalbergia latifolia at the New Forest and frequencies of almost all the ground vegetation have been recorded over a period of 1928-1949 (in some cases). These data have been examined and an effort has been made to correlate the frequencies of various species with the growth and development of tree species. Although, some correlation seems evident the data, have unfortunately, not been collected clearly enough to bring out exa.ct correlations. These data serve as a guide to lay properly further plots in the area.